2012
DOI: 10.4067/s0034-98872012001100009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación neuropsicológica en 129 pacientes chilenos con esclerosis múltiple recurrente remitente previo a inicio de fármacos inmunomoduladores

Abstract: Background: The detection of cognitive changes (CC) and psychiatric disorders in relapsing remitting multiple sclerosis (MS-RR (Rev Med Chile 2012; 140: 1437-1444.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(47 reference statements)
1
1
0
1
Order By: Relevance
“…Using the aforementioned criterion for defining abnormality showed that 35.5% of the patients had impairment. Similar figures were found by Nogales-Gaete et al 39 with a sample of Chilean patients with RRMS, but the finding here differs from other studies conducted in Oslo (Norway) and the UK and from another study in Spanish speaking patients in Argentina, 40 where the prevalence of cognitive impairment was >45%.…”
Section: Discussionsupporting
confidence: 82%
“…Using the aforementioned criterion for defining abnormality showed that 35.5% of the patients had impairment. Similar figures were found by Nogales-Gaete et al 39 with a sample of Chilean patients with RRMS, but the finding here differs from other studies conducted in Oslo (Norway) and the UK and from another study in Spanish speaking patients in Argentina, 40 where the prevalence of cognitive impairment was >45%.…”
Section: Discussionsupporting
confidence: 82%
“…Multiple sclerosis is a chronic disease, therefore long-term therapy constitutes the basis which apart from maintaining the patient's well-being should protect the patient from the disease relapses. Immunomodulating treatment uses interferon β-1-a and β-1-b, mitoxantrone, glatiramer acetate, natalizumab and fingolimod [ 12 14 ]. The choice of appropriate medication depends on the form and the kind of individual MS symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Realizamos: revisión de antecedentes demográficos, evaluación clínica neurológica, aplicación escala ampliada de discapacidad de Kurzke (EDSS), escala funcional compuesta, aplicación escala de intensidad de fatiga de Krupp, investigación de alteraciones cognitivas mediante batería neuropsicológica repetible breve de Rao (BNR-R) y manifestaciones depresivo-ansiosas mediante cuestionarios de Hamilton, Beck, o ambos. El análisis y versiones ocupadas en BNR-R y escalas de Hamilton o Beck están descritos en un trabajo previo nuestro 8 . Revisamos exámenes radiológicos registrando informes, observaciones complementarias y correlato con criterios de Barkhof-Tintoré 9 .…”
Section: Pacientes Y Métodounclassified